Evaluación post cosecha del café y propuesta de posicionamiento comercial para su exportación, de las zonas cafetaleras de Zumba, cantón y provincia de Zamora Chinchipe - Jaramillo Núñez, Alba Cecilia (2016)
This research called "coffee harvest Assessment and proposed trade position for export of coffee areas Zumba Region and province of Zamora Chinchipe" had the following objectives: Diagnose and characterize the post harvest handling of coffee and identification of critical points in the harvesting process - product sales; develop a proposal for post-harvest management - marketing based on the quality and safety conditions demanded by external markets that have trade agreements with associations of small producers; disseminate and share the results of research at the level of farmers, traders, retailers and the general public. The development work, beginning with the field phase or diagnosis of the current situation in the area around the production processes and post-harvest coffee, said investigative analysis had emphasized in the post process harvest, ie from harvest product to its marketing or sales. However the work supported by methodological investigative tools such as SWOT analysis systems, surveys, participatory workshops with farmers gave us important information about the production process significantly influences the quality of the product and therefore its profitability, specifically when the business transaction. These participatory workshops allowed us to understand somehow socioeconomic characteristics and peculiarities that justify the rational position and typological identification of the producer in their production declarations regarding the cultivation of coffee, especially: planting areas, consumer insight or market rates seeds, organic cultural processes, uncertainty in the sale, post-harvest handling, quality and safety markets, among others. These activities have allowed us to identify the current situation of the coffee produced in the area in relation to the cultivation and post-harvest coffee. Product recognition is made in support of these activities, using samples to an analysis of basic product quality in the study area, these are made with the support of the agricultural area Postharvest Laboratory of the National University of Loja. Subsequently, based on the identification of "problem" of coffee in the area, weaknesses and potential to improve the supply of marketing at the national and requirements implemented in the international market, a proposal around is made especially technical management Postharvest product having as reference the strategies presented in the SWOT analysis, national rules governing these processes, especially aimed at the sale in foreign markets. The level of organizational strengthening of the area to increase the supply under the procedures and rules requiring various foreign markets currently proposing strategies that make the association relationship, for both production and marketing. Also they arise as a result of participatory workshops a series of actions and / or recommendations for the short, medium and long term. For all that mentioned the level of production in the coffee sectors is still in small volumes due to improper handling in the production cycle, despite that have areas that have excellent natural conditions, suitable for obtaining a coffee with ecological quality, the largest market of production is sold directly to ACRIM and the rest is usually used for consumption and seed. Also the lack of infrastructure for the implementation of the methods of conventional wet processing, humid and wet enzyme do not let obtain washed coffees with organoleptic qualities of higher demand and prices, their knowledge is limited about physical, chemical and biological factors that influence or affect the various post harvest stages of coffee determining that improper practices affect the quality of the final product. To enhance the post production process of coffee, I recommend developing training programs especially in the Post harvest process, i.e. from harvest to marketing, applying good agricultural practices aimed at obtaining quality and safety of coffee, respecting the rules and international regulations required. Also, in a joint manner manage the producers and ACRIM to the current government to be part of the benefits they provide to the coffee sector itself. Keep a training program in its various stages, with the participation of the farmers and the general public that are part of the production chain and post production of coffee.